A new algorithm of global tightly-coupled transient heat transfer based on quasi-steady flow to the conjugate heat transfer problem. Issue 5 (September 2016) - Meng, Fanchao; Dong, Sujun; Wang, Jun; Guo, Dechun
Abstract: Concerning the specific demand on solving the long-term conjugate heat transfer (CHT) problem, a new algorithm of the global tightly-coupled transient heat transfer based on the quasi-steady flow field is further put forward. Compared to the traditional loosely-coupled algorithm, the computational efficiency is further improved with the greatly reduced update frequency of the flow field, and moreover the update step of the flow field can be reasonably determined by using the engineering empirical formula of the Nusselt number based on the changes of the inlet and outlet boundary conditions. Taking a duct heated by inner forced air flow heating process as an example, the comparing results to the tightly-coupled transient calculation by Fluent software shows that the new algorithm can significantly improve the computational efficiency with a reasonable accuracy on the transient temperature distribution, such as the computing time is reduced to 22.8% and 40% while the duct wall temperature deviation are 7% and 5% respectively using two flow update time step of 100 s and 50 s on the variable inlet-flow rate conditions. Highlights: An algorithm is put forward and implemented using OpenFOAM for long-term conjugate heat transfer (CHT) problem. Hypothesis of quasi-steady flow is verified acceptable to general CHT problem. Computational efficiency is further improved with greatly reduced flow update frequency. Update step of the flow can be reasonably determined using engineering empirical formula.